Metabolic, Environmental and Genetic Connection between Hepatocellular Carcinoma and Non-Alcoholic Fatty Liver Disease and its Application for Development of Novel Diagnostic and Therapeutic Tools - Jitendra Gupta, Reena Gupta (International Journal of Advanced Science and Technology, 2020)
Recently, the clinical cases of hepatitis C virus tend to decrease, and the prevalence of hepatocellular carcinoma (HCC) associated with non-alcoholic steatohepatitis (NASH) is expected to elevated as a result of the increasing epidemic of obesity and diabetes. The yearly incidence of the progression of HCC in subjects affected with NASH mediated hepatic cirrhosis is actually not known, but the rate is expected to be within the range between 2.6%-12.8%. Mounting novel mechanisms have been stated in the progression of HCC in NASH, but future prospective extended clinical studies are highly warranted to authenticate the clinical outcome. Recent clinical evidences show that the number of patients with non-alcoholic fatty liver disease and NASH is highly prone to HCC, even without cirrhosis. Resection of liver by detecting the affected portion and liver transplantation are the major therapeutic options in the management of NASH mediated HCC, but it imposes a significant burden and high treatment costs. Recently the prevalence of liver transplantation is increasing in NASH related HCC. Thus, clinicians have an important role to introduce accurate screening methods and therapeutic strategies precisely in NASH patients without cirrhosis in order to mitigate the HCC mediated by NASH.